POLA TABUHAN ALAT MUSIK PIDABAT DALAM IRINGAN TARI SIGAL PADA DAYAK BIDAYUH KABUPATEN BENGKAYANG - Vini Nopianti; Winda Istiandini; Chiristianly Yery Silaban (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2019)
AbstractThis research was motivated to know the Pidabat Music Instrument Punch Pattern in Sigal Dance Accompaniment on Celebration Bidayuh, Bengkayang Regency. The purpose of this research wasto describe ofPidabat Music Instrument Punch Pattern in Sigal Dance Accompaniment on Celebration Bidayuh, Bengkayang Regency. and descriptions design implementation research resulton activities learning in school.This research used descriptive method with  qualitative research. In this research using musicology approach. The data contained in this study were the results of direct observation and interviews whit informants relating about Pidabat Music Instrument Punch pattern in Sigal Dance Accompaniment on Celebration Bidayuh, Bengkayang Regency. The source of data is Ginop, Djupri, Ayak dan Lidianus.Data collection techniques are carried out by interview observation and documentation. The technique of validity examine was observation prolongation and tringualation technique. Based on data analysis, Pidabat music instrument has the three percussion pattern that is percussion pattern Selingan Biasa, Nyinok-nyinok and Ngolis-ngolis. in Pidabat music instrument this too has thetone blows “Dung” and “Pak”. The results of this study were expected to be implemented in a learning design in class VIII on Pidabat Music Instrument Punch Pattern in Sigal Dance Accompaniment Celebration Bidayuh,Bengkayang Regency. Key Words: Pidabat, Punch Pattern, Sigal Dance Accompaniment